2012
DOI: 10.1016/j.bbrc.2012.01.136
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Nox4 cytosolic domain produced by a cell or cell-free base systems exhibits constitutive diaphorase activity

Abstract: a b s t r a c tThe membrane protein NADPH (nicotinamide adenine dinucleotide phosphate) oxidase Nox4 constitutively generates reactive oxygen species differing from other NADPH oxidases activity, particularly in Nox2 which needs a stimulus to be active. Although the precise mechanism of production of reactive oxygen species by Nox2 is well characterized, the electronic transfer throughout Nox4 remains unclear. Our study aims to investigate the initial electronic transfer step (diaphorase activity) of the cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Normally, electron transfer from FAD to transmembrane heme groups is optimized by changes in protein conformation, as suggested for Nox2 (37). However, electron transfer from FAD to artificial substrates has been reported for Nox2 (62) and Nox4 (80,121,124). Whether in vivo the corruption of such dehydrogenase activity can generate ROS if these electrons are transferred to oxygen is interesting but yet speculative.…”
Section: Nox Nadph Oxidase Localization and Activation Within The Ermentioning
confidence: 99%
“…Normally, electron transfer from FAD to transmembrane heme groups is optimized by changes in protein conformation, as suggested for Nox2 (37). However, electron transfer from FAD to artificial substrates has been reported for Nox2 (62) and Nox4 (80,121,124). Whether in vivo the corruption of such dehydrogenase activity can generate ROS if these electrons are transferred to oxygen is interesting but yet speculative.…”
Section: Nox Nadph Oxidase Localization and Activation Within The Ermentioning
confidence: 99%
“…The family includes seven enzymes, which vary in structure, regulation, product and tissue distribution: Nox1 to Nox5, and dual oxidases (Duox), Duox1 and Duox2. One member – Nox4 – exists as two major isoforms, Nox4A and Nox4B . Given the significant role of the Nox family members in the production of ROS, therapeutic targeting of these enzymes in retinal vasculopathy has strong appeal.…”
Section: Introductionmentioning
confidence: 99%
“…However, two partners of Nox4 have been described recently: the protein disulfide isomerase (PDI) and the polymerase DNA directed-delta-interacting protein (Poldip2). Nox4 is unique among other Nox isoenzymes in that its activity is constitutive and may depend on a specific conformation of the dehydrogenase DH domain that should allow a spontaneous transfer of electrons from NADPH to FAD and to the hemes [24,25]. Data from various studies indicated clearly that Nox4 activity is regulated at the mRNA level, implying that an increase or decrease of ROS production by Nox4 is correlated to an up regulation [9,16,[26][27][28][29][30][31][32][33] or to a decline [34] of Nox4 transcripts.…”
Section: Introductionmentioning
confidence: 99%